The Evolution in the Management of Postbariatric Hypoglycemia: A Review and Comparison between International Guidelines from 2017 to 2024 - Abdelgadir, Elamin; Rashid, Fauzia; McGowan, Barbara (Journal of Diabetes and Endocrine Practice, 2025)
Postbariatric hypoglycemia (PBH) is an established complication of bariatric surgery, encountered especially after Roux-en-Y gastric bypass (RYGB). The sole manifestation is postprandial hyperinsulinemic hypoglycemia, which often takes place within the immediate 1 to 3 years postsurgery. Over the last decade, the knowledge of the PBH has robustly improved, and the management has evolved following a better understanding of its pathophysiology, advancements in diagnostic options, and the dynamic placement of therapeutic options. This review compares the three major available clinical consensus/guidelines published in 2017, 2022, and 2024, from different societies, respectively. Our report highlights the dramatic unfolding in diagnostic tools, dietary and pharmacological management, and, when needed, surgical interventions. This evolution of the guidelines reflects a consensus trend toward individualized, case-driven decision and management. Lately, the introduction of personalized dietary modification, adopting the approach of continuous glucose monitoring-assisted management response, and the advancement of pasireotide to be the second-line pharmacotherapy after the classical Acarbose were the highlights of the latest guidelines in 2024. This report will help understand and simplify the dynamic science in the relatively new field of PBH.
Keywords: bariatric surgery; dumping syndrome; guidelines; hypoglycemia; obesity; PBH; postbariatric